VET Data Report Germany 2023 : facts and analyses to accompany the Federal Government Report on Vocational Education and Training - selected findings - Le Mouillour, Isabelle [Herausgeber]; Neff, Daniel [Herausgeber] (Bundesinstitut für Berufsbildung, 2026)
"The Data Report of the Federal Institute for Vocational Education and Training (BIBB) provides a comprehensive overview of the actual data on the German Vocational Education and Training system and is published yearly in German. This current English version of the Data Report presents a selection of the most relevant data and analyses of the 2023 Data Report. It contains extensive information and analyses relating to initial and continuing vocational education and training and covers international indicators and benchmarks. The special focus of this Data Report is “Innovations in vocational education and training via programmes.”. The essential strength of the Data Report lies in the interplay between standardised reporting supported by time series and changing surveys that look at current developments and challenges. The overall picture it provides creates a central reference work on vocational education and training for the fields of academic research, policy and practice." (Editor, BIBB-Doku)
Keywords: G 1.3 Aus- und Weiterbildungsmarkt; S 2.3 Berufsbildungspolitik; S 1.3 Berufliche Erstausbildung; S 1.5.2 Berufliche Weiterbildung; 370; Berufsbildungsbericht; Berufsbildungsstatistik; Berufsbildungspolitik; Ausbildungsstellenmarkt; Monitoring; Betriebliche Berufsausbildung; Schulische Berufsausbildung; Ausbildungskosten; Berufliche Weiterbildung; Weiterbildungsförderung; Förderprogramm; Innovationspotenzial; Internationalisierung; Quantitative Angaben